Estimulantes alimentares para larvas de pacu - Tesser, Marcelo Borges; Portella, Maria Célia [UNESP] (FapUNIFESP (SciELO), 2011)
The present study aimed to investigate the stimulant effect of five amino acids (alanine, arginine, glycine, histidine and lysine) from betaine and their mixtures on the ingestion rates of formulated diet during the larval development of pacu Piaractus mesopotamicus. The statistical results showed significant effect of age and treatment. However, no significant effect was observed for the interaction of both factors. Glycine, lysine and betaine are considered good stimulants of the pacu feeding behavior.
Feeding stimulants for pacu lavae
Keywords: Amino acids; Ingestion rates; Piaractus mesopotamicus; Stimulants